Pendidikan Pesantren dan Kemandirian Santri - H.M. Djumransjah (Universitas Negeri Malang, 2016)
The aim of this study was to describe the development of continuing education programs to equip santri of pondok pesantren with knowledge and skills to support their lives. A case study design was implemented in this study which took place in Pondok Pesantren Nurul Jadid, Situbondo, East Jawa. The subjects were kyai, officials of the pesantren, ustad, santri and alumni of the pesantren selected purposively. The data were collected by interviews, observations and documents, and then analyzed by a reflective approach. It was found out that the pesantren has formulated their vision, mission, and (educational) aims. All of these were aimed to provide the santri with a broad spectrum of knowledge and skills, so that they will be able to earn for their living, and to help them prepare their lives in the hereafter